Effects of Chinese Shrimp (Fenneropenaeus chinensis) Stock Enhancement on the Fish Niche in a Mesocosm - Tao ZUO; Jingxian HUANG; Chuantao ZHANG; Jun WANG; Jianqiang SUN (Progress in Fishery Sciences, 2023)
Marine stock enhancement is not only commonly reported to amplify the target species production but also induces some potential threats or effects at multiple ecological levels in the receiving ecosystem. Studies on the interaction between released and naturally occurring organisms are necessary to avoid or minimize the adverse impacts of invasive species from stock enhancement in the receiving system. Chinese shrimp Fenneropenaeus chinensis, are an important stock enhancement species, and in recent years approximately 10 billion have been released annually into the coastal waters of China. Owing to fishing pressure and the ecological complexity of the open sea, the interaction between the released shrimp and native species may be weak and undetectable. Studies on the ecological impacts of such intensive releasing activities are limited. Therefore, in this study, an in-situ mesocosm experiment was carried out to determine if the released shrimp altered the relative composition and niche characteristics of fish, the results of which could serve as a reference to the local risk management of the species stock enhancement. The mesocosm was located in the shrimp-releasing channel of Weihe, Laizhou Bay, from April to September 2019. A cross design of four treatments with three replicates was conducted in the mesocosm. The habitats were homogenized across the replicates by mixing substrates and filtering seawater with a 0.28 cm sieve. The number of individual shrimp larvae released into net enclosures in each of the four treatments were: A) 2 400, B) 1 800, C) 1 200, and O) 0. The treatments were designed to represent the release of 1 billion, 750 million, 500 million, and no shrimp larvae (none-releasing) in the coastal waters of Laizhou Bay, respectively. The released shrimp larvae had an average body length of (1.63±0.18) cm and an average body width of (0.38±0.12) cm. At the end of the experimental period in September, shrimp and fishes were recaptured and their Levin's niche breadth and overlap indices were examined in each enclosure. Results indicated that within the enclosures of the four treatments, the recapture rates of shrimp ranged from 8.16% to 12.69% and had an average value of 9.87%. The number of recaptured shrimp increased with the number released, and had the highest value in enclosure A. However, the total biomass, average individual mass, and recapture rate of shrimp did not show a similar pattern among enclosures. The recapture rate of shrimp was significantly different among the treatments and had the highest value in enclosure C. The fish species composition was similar across all four treatment enclosures and included six species with three different feeding habits: Omnivores (Konosirus punctatus and Liza haematocheila), zooplanktivores (Thryssa mystax and Sardinella zunasi), and fish/shrimp predators (carnivores) (Acanthogobius sp. and Sparus microcephalus czerskii). Of the fish species, Acanthogobius sp. dominated in all enclosures, while S. m. czerskii occurred in only a few. There was no significant difference in the number and biomass of total fishes and carnivorous fishes among enclosures. There were more omnivorous fishes in the released enclosures A–C, while the number of zooplanktivorous fishes decreased when shrimp were released and had the highest number and biomass in the non-released enclosure O. Moreover, fishes with different feeding habits had variable niche breadths among the four treatment enclosures. Most fish species had a wider niche breadth in enclosures with released shrimp (enclosure A–C) than in enclosure O. Both the fish´s niche overlap indices and the species pairs with high niche overlap (> 0.75) decreased in the order non-released enclosure O > released enclosure B > enclosure C > enclosure A. The carnivorous fish Acanthogobius sp. had more pairs with niche overlap indices (> 0.75) in the non-released enclosure O than in the other three treatments. A similarity analysis and multidimensional plot indicated that enclosures A and O could be differentiated by the relatively long similarity distance and little overlap area. The results of the experiment suggest that the shrimp recapture efficiency did not increase when shrimp were released. In the waters of the study area, released shrimp could have a positive effect on the total output of both shrimp and fish, especially for omnivorous and carnivorous fishes, as the shrimp could share predation pressure and provide food for them. In addition, the shrimp release may affect the relative composition and niche characteristics of fish by increasing their niche breadth and reducing the overlap between fishes with different feeding habits, and the impacts may be more detectable as the shrimp number increases.